Aggregated Semantic Matching for Short Text Entity Linking - Nie, Feng; Zhou, Shuyan; Liu, Jing; Wang, Jinpeng; Lin, Chin-Yew; Pan, Rong (Conference on Computational Natural Language Learning, 2018)
The task of entity linking aims to identify concepts mentioned in a text fragments and link them to a reference knowledge base. Entity linking in long text has been well studied in previous work. However, short text entity linking is more challenging since the text are noisy and less coherent. To better utilize the local information provided in short texts, we propose a novel neural network framework, Aggregated Semantic Matching (ASM), in which two different aspects of semantic information between the local context and the candidate entity are captured via representation-based and interaction-based neural semantic matching models, and then two matching signals work jointly for disambiguation with a rank aggregation mechanism. Our evaluation shows that the proposed model outperforms the state-of-the-arts on public tweet datasets.